Osteochondritis Dissecans: Current Understanding of Epidemiology, Etiology, Management, and Outcomes. (16th June 2021) - Chau, Michael M.; Klimstra, Mikhail A.; Wise, Kelsey L.; Ellermann, Jutta M.; Tóth, Ferenc; Carlson, Cathy S.; Nelson, Bradley J.; Tompkins, Marc A.
Abstract : Osteochondritis dissecans occurs most frequently in the active pediatric and young adult populations, commonly affecting the knee, elbow, or ankle, and may lead to premature osteoarthritis. While generally considered an idiopathic phenomenon, various etiopathogenetic theories are being investigated, including local ischemia, aberrant endochondral ossification of the secondary subarticular physis, repetitive microtrauma, and genetic predisposition. Diagnosis is based on the history, physical examination, radiography, and advanced imaging, with elbow ultrasonography and novel magnetic resonance imaging protocols potentially enabling early detection and in-depth staging. Treatment largely depends on skeletal maturity and lesion stability, defined by the presence or absence of articular cartilage fracture and subchondral bone separation, as determined by imaging and arthroscopy, and is typically nonoperative for stable lesions in skeletally immature patients and operative for those who have had failure of conservative management or have unstable lesions. Clinical practice guidelines have been limited by a paucity of high-level evidence, but a multicenter effort is ongoing to develop accurate and reliable classification systems and multimodal decision-making algorithms with prognostic value.